Erectile Dysfunction Is Positively Correlated with Mean Platelet Volume and Platelet Count, but Not with Eosinophil Count in Peripheral Blood - Otunctemur, Alper; Bozkurt, Muammer; Besiroglu, Huseyin; Polat, Emre Can; Ozcan, Levent; Ozbek, Emin (Urology Journal, 2015)
Purpose: Increased eosinophil count (EC), mean platelet volume (MPV), and platelet count (PC) are important in vascular disorders which are main factors resulting in endothelial dysfunction. We aimed to investigate the association between MPV, and EC, with erectile dysfunction (ED). Materials and Methods: Two hundred thirty participants (130 patients with ED, and 100 healthy controls) were enrolled in this study. A detailed psychosexual history obtained, and physical, and laboratory examination were performed. International Index of Erectile Function (IIEF)-5 questionnaire was used to evaluate the erectile status objectively. IIEF-5 score was applied to all patients, and IIEF-5 score under 22 was considered as ED. The MPV, PC, and EC were compared between the two groups. Results: The mean age of the patients with ED and control group was 55.62 ± 8.90 years and 54.19 ± 4.10 years, respectively. MPV and PC levels were significantly higher in ED group (8.51± 1.00 fL and 8.16 ± 0.94 fL; 244.59 ± 57.3 cells/µL and 230.17 ± 48.44 cells/µL, respectively (P < .05). EC and white blood cell count were not significantly different between study and control groups. Conclusions: In our study a relationship was found between elevated MPV, and PC with ED. MPV and PC may be used as a biomarker in patients with ED.